Mission as action in hope in the context of white poverty in Pretoria: a case for Betlehem Mission Centre - D. Mashau (Acta Theologica)
The gap between the rich and the poor is widening daily and the proportion of people living in poverty in South Africa is steadily on the rise. The phenomenon of white poverty has existed since the 1890s and is becoming a more common trend across South Africa. White poverty left a number of whites in South Africa homeless. Consequently, they are forced to live in the streets, in shelters and informal settlements such as Bethlehem Mission Centre in Pretoria. A descriptive study was undertaken within the qualitative paradigm to describe the living conditions at the Bethlehem Mission Centre in Pretoria. The mission operandi, faith-based focus and funding of the Centre is described. In describing the experience of people involved in Bethlehem Mission Centre a story unfolds of how hope may be restored to a seemingly hopeless situation. The church living out “mission as action in hope” can address the issue of poverty in the context it serves.